IDENTIFYING MOTIVATIONAL FACTORS RESPONSIBLE FOR ESTABLISHMENT OF MSME: A CASE STUDY OF UDALGURI DISTRICT, BTR, ASSAM - 1. Phung Roje Muchahary , 2. Dr. Pradip Brahmachary (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
This paper is an attempt to explore the factors responsible for establishment of MSMEs in Udalguri district, located in the Bodoland Territorial Region (BTR) of Assam, India. The study is primarily based on primary data collected through questionnaires based on information gathered from MSMEs owners registered under DICC for the year 2010 to 2019. The analysis is carried out with help tools like Likert scale, Chi-square, percentage method and Garret score. The study reveals that the majority of MSMEs in the region are micro-enterprises, with a significant presence of small-scale enterprises. Male entrepreneurs dominate the sector, but there is noteworthy participation from female entrepreneurs. The main motivations for entering the MSME sector are identified as self-employment, personal passion, and the potential for additional income. The research employs the Garrett ranking technique to ascertain the most influential factors driving entrepreneurs to establish MSMEs. Self-employment emerges as the most significant motivator, followed by personal passion and additional income opportunities. This study not only sheds light on the diverse landscape of MSMEs in Udalguri district but also underscores the pivotal role these enterprises play in job creation and economic development. The findings underscore the paramount importance of comprehending entrepreneurial motivations to devise policies that nurture the growth and sustainability of MSMEs in this region.